(untitled) (Al-Farooq Journal of Sciences, 2026)
Green education is considered one of the modern concepts aimed at enhancing environmental awareness and embedding sustainability principles within educational institutions by linking theoretical knowledge with practical practices related to the protection of natural resources, particularly water resources. The importance of this approach has increased in light of the growing environmental problems resulting from unsustainable agricultural practices, most notably soil and groundwater contamination with nitrates caused by the excessive use of fertilizers and irrigation water. This research aims to highlight the role of green education in promoting water sustainability awareness and reducing soil and groundwater nitrate pollution by shedding light on the relationship between irrigation practices and nitrate transport in soil, as well as emphasizing the importance of environmental awareness in rationalizing the use of water and fertilizers. The study also reviews the concepts of green education and water sustainability, and the role of educational institutions in spreading a culture of sound water resource management. The study adopted the descriptive-analytical approach, based on a review of scientific literature related to green education and environmental sustainability, in addition to employing applied results derived from a previous study on nitrate transport in soil under irrigation influence. The findings revealed that increased irrigation amounts and improper fertilizer management lead to enhanced nitrate leaching into deeper soil layers, thereby increasing the risk of groundwater contamination and negatively affecting the environment and public health. The study concludes that integrating water sustainability concepts into green education programs contributes to promoting responsible environmental behavior, spreading a culture of sustainable irrigation, and reducing practices that lead to water resource pollution. It also recommends strengthening educational and awareness programs related to sustainable water management within educational institutions, and encouraging the application of practical environmental models that support the protection of natural resources and the achievement of sustainable development.